2016
DOI: 10.1007/s10545-015-9912-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a higher dose of alglucosidase alfa on ventilator‐free survival and motor outcome in classic infantile Pompe disease: an open‐label single‐center study

Abstract: BackgroundThough enzyme-replacement therapy (ERT) with alglucosidase alfa has significantly improved the prospects for patients with classic infantile Pompe disease, some 50 % of treated infants do not survive ventilator-free beyond the age of 3 years. We investigated whether higher and more frequent dosing of alglucosidase alfa improves outcome.MethodsEight cross-reactive immunological material (CRIM) positive patients were included in the study. All had fully deleterious mutations in both GAA alleles. Four r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 28 publications
3
85
1
3
Order By: Relevance
“…Early initiation of rhGAA infusion after diagnosis through NBS improves the outcomes of IOPD, but muscle weakness, ptosis, and speech disorders still occurred [7], [17]. An increase in the dosage or frequency of rhGAA infusion appears to provide some benefits to these patients but is not sufficient to prevent residual symptoms [7], [22], [23]. In the current study, we demonstrated that albuterol speeded the climb of patients and selectively improved muscle function and movement quality, but we could not prove its benefit in the 6MWT consistently nor its significant benefit in other measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of rhGAA infusion after diagnosis through NBS improves the outcomes of IOPD, but muscle weakness, ptosis, and speech disorders still occurred [7], [17]. An increase in the dosage or frequency of rhGAA infusion appears to provide some benefits to these patients but is not sufficient to prevent residual symptoms [7], [22], [23]. In the current study, we demonstrated that albuterol speeded the climb of patients and selectively improved muscle function and movement quality, but we could not prove its benefit in the 6MWT consistently nor its significant benefit in other measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent advances in immune modulation with ERT have enhanced survival in CRIM‐negative patients and these patients have a new and emerging phenotype but data on pulmonary function tests has yet to be collected 54 . We will need to evaluate more of the patients with IPD over time to assess the impact of genotype, ACE genotype, CRIM status, and dose escalation on the rate of decline of FVC 19,22,41 . Finally, because these children had variable efforts with their maximal inspiratory and expiratory strengths measurements, these data were difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the increased effectiveness of higher doses of enzyme replacement therapy in infantileonset Pompe disease. 5,6,11 Case et al (2015) demonstrated the efficacy of alternative enzyme replacement therapy regimens (high frequency at 20 mg/kg weekly or high dose at 40 mg/kg every 2 weeks) in initially responsive patients who had experienced declining function on standard enzyme replacement therapy (20 mg/kg every 2 weeks). 5 Their patients demonstrated an overall trend for motor improvement from baseline after 52 weeks of the more intensive enzyme replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…van Gelder et al (2016) reported that their data may suggest that a dose of 40 mg/kg weekly vs the currently recommended dose of 20 mg/kg every 2 weeks improves outcomes for CRIM-positive patients. 6 New trials in Pompe disease based on gene therapy are currently ongoing. 12 However, treatment of severe cardiac disease remains quite challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation